Intra-Arterial Prostaglandin E1 Infusion in Patients with Rest Pain: Short-Term Results - A. Chatziioannou; A. Dalakidis; K. Katsenis; V. Koutoulidis; D. Mourikis (The Scientific World Journal)
Purpose. To present our results after short-term (1 month) intra-arterial infusion therapy of PGE1-alprostadil via a port system implanted in the ipsilateral external iliac artery (EIA) in patients with severe rest pain. Methods. Ten patients with severe rest pain were included. All patients showed extensive peripheral vascular disease below the knee. The tip of the catheter was introduced via a retrograde puncture in the ipsilateral external iliac artery (EIA). The patients received intraarterial infusion of PGE1, 20 mgr alprostadil daily, via the port catheter for 1 month. Results. Clinical success was evaluated according to subjective grading of pain (group A significant decrease, group B moderate decrease and group C no response). A significant decrease of rest pain was observed in 8 (group A, 80%) patients, a moderate decrease in 2 (Group B, 20%), whereas no patients demonstrated any significant response. Both patients of group B had Buergers' disease and continue to smoke during therapy. No peripheral thrombosis or clinical deterioration was noticed. Conclusion. Intraarterial infusion of PGE1 alprostadil on a daily basis, using a port catheter into the ipsilateral EIA, in selected patients with severe rest pain, seems to be very effective, without any serious complications.